Pandemics And Infodemics: The Narrative Of Uncertainty And The Uncertainty Of The Narrative - Bakezzi, Soumia (المجلة الجزائرية للأمن الإنساني, 2024)
It has now become something of a commonplace to accuse New Media of the unwelcomed ramifications it has caused in the arena of information in what has been recently labeled ‘disinformation’ and ‘infodemics’. The issue surely took on a heightened significance within the context of the recent pandemic, as the subversion of the official story and medical opinion on the matter crystallized in a distinctive way so as to compromise amorphous truth and knowledge in favor of a wholesome picture that explains their frailty vis-a-vis the waves of infodemics which correlated with those of the pandemic. While we acknowledge that the scale at which this has been done is hitherto unprecedented due to the interconnectedness of the world, we posit that the history of sober events has never been inoculated from infordemics and by extension uncertainty. And while the term infodemics may seem an anachronistic concept, it still accounts for the spread of non-official narratives in a heuristic way. In this paper, we aim to highlight the precariousness of the metanarrative of the pandemic vis-a-vis a rising counternarrative and how it is conducive to uncertainty. The article integrates three strands of knowledge. First by foregrounding the insight that information does not equal knowledge which explains the rise in competing information. Second, by considering how metanarrative is convertible into infodemics, we account for an historical upscaling of infodemics and how they arise as a counterbalance in the imbalance of power structure. Lastly, we make implicit the hypothesis that sober events are candidates for the hijack of infodemics and how an elected comprehensive narrative, in the Darwinian sense, is likely to overrun even the information deemed ‘scientific’. We will do so by considering the literature on pandemics as well as by exploring the links between pandemics and infodemics. I situate this in relation to contemporary discussion about COVID-19 and infodemics, but only in conjunction with previous episodes of pandemics (and even epidemics), I argue, does the picture yield a meaningful interpretation.